2016
DOI: 10.1080/00071668.2016.1141171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an organic acid blend and essential oil blend, individually or in combination, on growth performance, carcass parameters, apparent digestibility, intestinal microflora and intestinal morphology of broilers

Abstract: This study aimed to evaluate the influence of an organic acid (OA) and essential oil (EO) blends, individually or in combination, on growth performance, carcass parameters, apparent digestibility, intestinal microflora and intestinal morphology of broilers. A total of 480 one-d-old male Ross 308 chicks were randomly assigned to 4 treatments consisting of 4 replicates each (n = 30 birds in each replicate). Dietary treatments consisted of a basal diet (control), and basal diet supplemented with 2 g/kg OA blend (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
8
18
0
Order By: Relevance
“…Several in vivo studies indicated that essential oils increased the Lactobacillus group and decreased E. coli or total coliforms in piglets ( Namkung et al., 2004 , Castillo et al., 2006 , Li et al., 2012 , Zeng et al., 2015 , Wei et al., 2017 ). These results were consistent with the results observed in several poultry studies with the supplementation of essential oils ( Oviedo-Rondón et al., 2006 , Tiihonen et al., 2010 , Amerah et al., 2011 , Basmacioglu-Malayoglu et al., 2016 , Cetin et al., 2016 , Liu et al., 2017 ), suggesting that essential oil treatment led to some fundamental changes within gut microbiota mainly in the number of observed Lactobacillus species. However, studying the effects of essential oils on the gut microbiome of pigs with integrated approaches (e.g., various molecular and “omics” technologies as well as bioinformatics and statistical analyses) is still needed in order to comprehensively monitor the shifts in composition and functionality of the microbiota in response to dietary essential oils treatments.…”
Section: Effect Of Essential Oils On Intestinal Microbiota and Microbsupporting
confidence: 91%
“…Several in vivo studies indicated that essential oils increased the Lactobacillus group and decreased E. coli or total coliforms in piglets ( Namkung et al., 2004 , Castillo et al., 2006 , Li et al., 2012 , Zeng et al., 2015 , Wei et al., 2017 ). These results were consistent with the results observed in several poultry studies with the supplementation of essential oils ( Oviedo-Rondón et al., 2006 , Tiihonen et al., 2010 , Amerah et al., 2011 , Basmacioglu-Malayoglu et al., 2016 , Cetin et al., 2016 , Liu et al., 2017 ), suggesting that essential oil treatment led to some fundamental changes within gut microbiota mainly in the number of observed Lactobacillus species. However, studying the effects of essential oils on the gut microbiome of pigs with integrated approaches (e.g., various molecular and “omics” technologies as well as bioinformatics and statistical analyses) is still needed in order to comprehensively monitor the shifts in composition and functionality of the microbiota in response to dietary essential oils treatments.…”
Section: Effect Of Essential Oils On Intestinal Microbiota and Microbsupporting
confidence: 91%
“…Herbal essential oils in diet improved the villus width and height in the jejunum and ileum of quail breeders (Hajiaghapour & Rezaeipour, 2018). Broilers fed on the organic acid blends and essential oil blends had higher villus height and lower crypt depth in the ileum (Basmacioğlu-Malayoğlu, Ozdemir, & Bağriyanik, 2016). Consistent with those earlier studies, we observed that HEM improved intestinal morphology through increased the ratio of villus height to crypt depth in two small intestine segments of duodenum and jejunum, and HEM had the same effect to intestinal morphology with antibiotics.…”
Section: Ta B L Ementioning
confidence: 96%
“…In broilers, the dietary supplementation with organic acid improved body weight gain and feed efficiency when compared with control. But, dietary organic acids had no significant impacts on feed intake or relative organ weights (Basmacioğlu‐Malayoğlu, Ozdemir, & Bağriyanik, ).…”
Section: Role Of Acidifiers In Nutritionmentioning
confidence: 99%